Menopause knowledge and experience for a group of women - Costa, Gabriela Maria C; Gualda, Dulce Maria Rosa (Revista da Escola de Enfermagem da USP, 2008)
This ethnographic study is aimed at understanding a group of women's knowledge about menopause and how they experience it. The methods used for data collection were participant observation, recorded interviews and previously produced drawings. Data were analyzed based on a theoretical framework using both the ethnographic method and biographic interpretativism. From the narratives the authors obtained the cultural categories and themes. Thus it was possible to conclude that menopause is understood as a result of a unique construction integrated to a network of meanings built by the group that condition knowledge and experience within certain cultural patterns, among them the fact that menopause means leaving womanhood behind.